Sophisticated bibliometrics - Aguillo, Isidro F. (Anuario ThinkEPI, 2022)
A call to apply a more sophisticated, professional bibliometrics based on technical and scientific quality metrics that overcomes the current easy though incorrect practices in the evaluation processes of scientific activity.